Algorithm Design and Programming the Luenberger Observer for level estimation in a Storage Tank System - Mursyitah, Dian; Faizal, Ahmad; Sari, Sitri Permata (Institut Riset dan Publikasi Indonesia, 2025)
This study presents the design and implementation of a Luenberger Observer algorithm for state estimation in a liquid storage tank system. The methodology includes system parameter identification, data preprocessing, observer gain calculation using pole placement, and simulation in MATLAB and Simulink. To reflect real-world conditions, synthetic disturbances were added and the input signal was normalized to improve numerical stability. Quantitative evaluation was conducted by comparing the system output with the observer’s estimated output. Simulation results demonstrate that the observer effectively tracks the system dynamics, yielding a root mean square error (RMSE) of 7×10?? m and a near-zero steady-state error. The observer's robustness was also tested systematically through increasing levels of synthetic measurement noise, showing stable and accurate performance even under 6% noise conditions. These findings confirm that the proposed algorithm provides reliable and responsive state estimation, with strong potential for practical application in control systems for dynamic fluid environments